Heteroatom Cycloaddition at the (BN)2 Bay Region of Dibenzoperylene. (11th June 2021) - Fingerle, Michael; Dingerkus, Juliane; Schubert, Hartmut; Wurst, Kai M.; Scheele, Marcus; Bettinger, Holger F.
Abstract: Cycloaddition‐dehydration involving a BNBN‐butadiene analogue at the bay region of a dibenzoperylene and a non‐enolizable aldehyde provides a novel strategy for incorporation of the oxadiazadiborinane (B2 N2 CO) ring into the scaffold of a polycyclic aromatic hydrocarbon resulting in highly emissive compounds. Abstract : We report the first acid‐catalyzed heteroatom cycloaddition at the (BN)2 bay region of a dibenzoperylene with different aldehydes. This new method allows the synthesis of heteroatom‐doped polycyclic aromatic hydrocarbons (PAHs) and the formation of 1, 3, 5, 2, 4‐oxadiazadiborinane (B2 N2 CO) rings.